Movement patterns of juvenile whale sharks tagged at an aggregation site in the Red Sea. - Michael L Berumen; Camrin D Braun; Jesse E M Cochran; Gregory B Skomal; Simon R Thorrold (PLoS ONE, 2014)
Conservation efforts aimed at the whale shark, Rhincodon typus, remain limited by a lack of basic information on most aspects of its ecology, including global population structure, population sizes and movement patterns. Here we report on the movements of 47 Red Sea whale sharks fitted with three types of satellite transmitting tags from 2009-2011. Most of these sharks were tagged at a single aggregation site near Al-Lith, on the central coast of the Saudi Arabian Red Sea. Individuals encountered at this site were all juveniles based on size estimates ranging from 2.5-7 m total length with a sex ratio of approximately 1∶1. All other known aggregation sites for juvenile whale sharks are dominated by males. Results from tagging efforts showed that most individuals remained in the southern Red Sea and that some sharks returned to the same location in subsequent years. Diving data were recorded by 37 tags, revealing frequent deep dives to at least 500 m and as deep as 1360 m. The unique temperature-depth profiles of the Red Sea confirmed that several whale sharks moved out of the Red Sea while tagged. The wide-ranging horizontal movements of these individuals highlight the need for multinational, cooperative efforts to conserve R. typus populations in the Red Sea and Indian Ocean.